Information Technology and the Improvement of Public Services in Village Government - Anggelina Wokanubun; Semuel Willem Sipahelut; Selvia F. G. Renyut (Univiversitas Dr. Djar Wattiheluw, 2025)
This study examines the impact of information technology (IT) utilization on public service delivery within the Ohoi Rumaat village administration, Kei Kecil Timur District, Southeast Maluku Regency. Using a quantitative approach and analyzed through PLS-SEM, data were collected from 71 respondents selected via non-probability sampling based on the Slovin formula. The findings reveal that IT use has a significant and positive effect on service quality, supported by a path coefficient of 0.653, a T- statistic of 9.329, and a P-value of 0.000. The R2 value of 0.427 indicates that IT accounts for 42.7% of the variance in public service quality. These results emphasize the role of digitalization in improving efficiency, transparency, and citizen participation in village governance. The study supports the relevance of Innovation Diffusion Theory in rural settings and calls for strategic integration of IT with adequate infrastructure, human resource development, and supportive policies for sustainable digital transformation.